Novel Strategy for Sulfapyridine Detection Using a Fully Integrated Bio-MEMS: Application to Honey Analysis. (2017) - Hassani, Nadia El Alami El; Baraket, Abdoullatif; Neto, Ernandes Taveira Tenório; Lee, Michael; Salvador, Juan Pablo; Colas, Maria pilar Marco; Bausells, Joan; Bari, Nezha El; Bouchikhi, Benachir; Elaissari, Abdelhamid; Errachid, Abdelhamid; Zine, Nadia
Abstract: Sulfapyridine (SPy) as a category of sulfonamides, have been widely used as veterinary drugs for prophylactic and therapeutic purposes. However, several classes of bacteria have become resistant to this drugs due to their abusive uses. This practice can also signify a potential risk to human health since many diseases may emerge, such as thyroid cancer and anaphylactic reactions. We report in the present work the development of a highly sensitive Biomicro-electro-mechanical systems (BioMEMS) gold transducers as working micro electrodes (WEs) for the detection of SPy residues in honey at the low ppb concentration. The detection of SPy by this method is highly promising to give a stable measurement and a rapid response, with a detection limit of 0.28 ng kg -1 in honey.